2019
DOI: 10.1016/j.ijdevneu.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal anoxia impairs long‐term energy metabolism and somatic development of Wistar rats

Abstract: Background: Neonatal anoxia may cause neurological injuries, behavioral alterations and changes in somatic growth. Somatic developmental changes suggest a possible effect of anoxia on energy metabolism and/or feeding behavior. Short-term effects of oxygen deficit on energy homeostasis have been described. In contrast, just a few studies report long-term effects. This study investigated the effects of neonatal anoxia on energy metabolism and somatic development at adulthood of males and females Wistar rats. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 76 publications
4
15
0
Order By: Relevance
“…The condition is aggravated in low-weight preterm newborns, which accounts for 60% of the incidence of HI, which leads to long-term negative effects on motor, sensory, and cognitive development due to brain injury [1, 2]. Previous studies of our research group revealed that the global and noninvasive NA model, validated by Takada et al [2], (1) triggered a decrease in total hippocampal volume [3, 4], (2) decreased performance in spatial memory [5, 6], (3) showed sex-dependent differences concerning sensorimotor deficits [7], and (4) further described long-term metabolic and somatic development impairments related to NA outcomes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The condition is aggravated in low-weight preterm newborns, which accounts for 60% of the incidence of HI, which leads to long-term negative effects on motor, sensory, and cognitive development due to brain injury [1, 2]. Previous studies of our research group revealed that the global and noninvasive NA model, validated by Takada et al [2], (1) triggered a decrease in total hippocampal volume [3, 4], (2) decreased performance in spatial memory [5, 6], (3) showed sex-dependent differences concerning sensorimotor deficits [7], and (4) further described long-term metabolic and somatic development impairments related to NA outcomes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal anoxia differently affects the body's energy metabolism, according to sex and age (Cruz‐Ochoa et al., 2019). This stimulus affects the development of both sexes differently: while anoxic male weighs more than their control, the female show no changes in the weight compared with their control group.…”
Section: Discussionmentioning
confidence: 99%
“…Short‐ and long‐term neurodevelopmental abnormalities by neonatal anoxia are reproduced in neurological reflexes and motor coordination, which can assess brain maturation during neonatal development (Cruz‐Ochoa et al, 2019; Lubics et al, 2005; Smart & Dobbing, 1971). We have induced the anoxia in full‐term (30 h age) pups by providing 100% nitrogen, which mimics the human neonatal anoxic conditions in preterm babies (6 gestational months) (Kumar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We also noticed a significant decrease in cliff avoidance response in anoxic pups, suggesting that anoxic injury to pups resulted in the loss of coordination between vibrissae and locomotor output. Neurodevelopmental deficits following anoxic injury are proportional to a decline in somatic growth (Cruz‐Ochoa et al, 2019; Kumar et al, 2017). We found that I3C treatment increased the somatic growth of anoxic pups, implying body growth and brain development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation